1710. Comparison of herpes simplex prevalence in serum and semen-cervical sample of infertility patients: A systematic review and meta-analysis. (31st December 2020) - Chiu, Chia-Yu; Sarwal, Amara; Yangga, Peter; Feinstein, Addi; Hennessey, Karen
Abstract: Background: Herpes simplex virus (HSV) is a common pathogen of sexually transmitted infections, however the role it plays in the development of infertility is unknown. In animal studies, inoculating murine rete testis with HSV-1 revealed irreversible atrophy of the germinal epithelium. Another study found that human herpesvirus 1 thymidine kinase (HHV-1 TK) protein disrupts spermatogenesis by creating immature sperm and accelerating apoptotic cell death in rodent. Although it is well established that herpes virus affects fertility in male animal models, the question remains as to the effect of HSV in human infertility. Routine testing of serum HSV IgG/IgM/DNA or HSV PCR in semen-cervical sample is not commonly done in clinical practice, and there are no set guidelines as when to screen. We aim to review the available literature and compare the prevalence of HSV in serum versus semen-cervical samples, focusing on the infertile patient population. Methods: We searched PubMed, Embase, Cochrane Library, and ClinicalTrials.gov from inception to December 2019. Our search terminology included: "Herpes, Human herpesvirus, infertility." Inclusion criteria required testing to be done on either serum, sperm, menstrual fluid, or endocervical sample in infertile patients. PRISMA Flow Diagram for study selection. Results: 17 retrospective studies were included in this review. In the male-infertility cohort, a total of 11 studies were compared. The random-effects pooled prevalence was 12.7% in semen sample, and 16.8% in serum sample. In the female-infertility cohort, a total of 6 studies were compared. The random-effects pooled prevalence was 12.1% in menstrual fluid /endocervical sample, and 17.8% in serum sample. Figure 1. Studies enroll in this meta-analysis, Male Figure 2. Studies enroll in this meta-analysis, Female Conclusion: The prevalence of HSV in semen-cervical sample was about 12%, compared to HSV in serum sample is about 17%. Therefore, HSV contribution to infertility will be overestimated when we use serum sample for diagnosis. It is noteworthy to mention that the seroprevalence of HSV IgG is much higher in general population, previously reported at 35% to 50%. In addition, given that current antiviral treatment for HSV has side effects that could cause infertility on its own, as seen in animal studies. More studies are needed to evaluate the role HSV plays in causation of infertility. Disclosures: All Authors : No reported disclosures